The Surface Coverage and Corrosive Rate of Methanol Extract from Taro Tuber (Colocasia esculenta) on Mild Steel in Sulfuric Acid - Gusti, Diah Riski (Journal of Chemical Natural Resources, 2019)
Surface coverage and corrosion rate of taro tuber methanol extract on mild steel in dilute 0.5 M sulfuric acid solution were studied through weight loss method, FT-IR spectroscopy and SEM.The result obtained in 0.5 M sulfuric acid solution for 72 hours with optimal surface coveragewas 0.86. The corrosion ratewas found to be decreased and surface coveragewas increased with the increasing concentration of taro tuber methanol extract which was added. The results showed that taro tuber methanol extract was a good corrosion inhibitor.